Cooperative learning for intercultural classrooms case studies for inclusive pedagogy - Ferguson-Patrick, Kate; Jolliffe, Wendy (Routledge, 2018)
"Cooperative Learning for Intercultural Classrooms helps both pre-service and in-service teachers to develop a well-researched pedagogy that supports inclusive practice for a globalised world. It provides: an overview of theoretical perspectives that illustrate why cooperative learning is an effective learning strategy; reviews research findings about how cooperative learning supports inclusion; and outlines the strategies and methods that support teachers in putting cooperative learning into practice."--Provided by publisher.